2012
DOI: 10.1111/j.1558-5646.2012.01590.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis of Adaptation in Arabidopsis Thaliana: Local Adaptation at the Seed Dormancy QTL Dog1

Abstract: Local adaptation provides an opportunity to study the genetic basis of adaptation and investigate the allelic architecture of adaptive genes. We study DELAY OF GERMINATION 1 (DOG1), a gene controlling natural variation in seed dormancy in Arabidopsis thaliana and investigate evolution of dormancy in 41 populations distributed in four regions separated by natural barriers. Using The genetic basis of local adaptation is one of the fundamental questions in evolutionary biology. Local adaptation occurs if selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
144
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(153 citation statements)
references
References 92 publications
8
144
1
Order By: Relevance
“…Interestingly, dormancy variation in Arabidopsis populations is associated with a series of functionally distinct alleles showing InDel variations in intron 1 that segregate at the AtDOG1 locus, which probably reflects local environmental adaptation (Kronholm et al, 2012). Although this does not generate any causal relationship, it demonstrates that for the interspecies comparison, a combination between exon sequence conservation (suggesting common function) and intron divergence (suggesting local environmental adaptation and/or speciation) is evident as well.…”
Section: Discussion Spatiotemporal Maturation Patterns In L Papillosmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, dormancy variation in Arabidopsis populations is associated with a series of functionally distinct alleles showing InDel variations in intron 1 that segregate at the AtDOG1 locus, which probably reflects local environmental adaptation (Kronholm et al, 2012). Although this does not generate any causal relationship, it demonstrates that for the interspecies comparison, a combination between exon sequence conservation (suggesting common function) and intron divergence (suggesting local environmental adaptation and/or speciation) is evident as well.…”
Section: Discussion Spatiotemporal Maturation Patterns In L Papillosmentioning
confidence: 99%
“…The phenomenon that the maternal environment during seed development and maturation determines the germination phenology of Arabidopsis and other species is well-established knowledge (Kugler, 1951;Gutterman, 1980Gutterman, /1981Munir et al, 2001). However, as a major advance, we now know from ecological work with Arabidopsis (Huang et al, 2010;Moyers and Kane, 2010;Chiang et al, 2011;Barua et al, 2012;Kronholm et al, 2012) that natural genetic variation at the DOG1 locus is a major determinant for the local adaptation to novel environments, and we also know that the maternal environment controls DOG1 gene expression during seed maturation. For example, low temperature during seed maturation causes increased DOG1 gene expression and deeper primary dormancy of mature seeds (Chiang et al, 2011;Kendall et al, 2011;Nakabayashi et al, 2012).…”
Section: Discussion Spatiotemporal Maturation Patterns In L Papillosmentioning
confidence: 99%
See 2 more Smart Citations
“…Ecophysiological work has shown that seed dormancy is a crucial fitness component with far-reaching consequences for the evolution of entire life histories (1)(2)(3). As an innate seed property, seed dormancy defines the environmental conditions in which a seed is able to germinate and ensures that the most vulnerable later phases of the plant life cycle occur during favorable seasonal and environmental conditions.…”
mentioning
confidence: 99%